2010
DOI: 10.1002/14651858.cd006478.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Topical silver for preventing wound infection

Abstract: There is insufficient evidence to establish whether silver-containing dressings or topical agents promote wound healing or prevent wound infection; some poor quality evidence for SSD suggests the opposite.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
169
0
7

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 192 publications
(182 citation statements)
references
References 71 publications
3
169
0
7
Order By: Relevance
“…The silver dressing did not increase the overall healing rate, but it was associated with quicker healing in larger and older ulcers. An extensive metastudy by Storm-Versloot et al 79 confirmed these findings in that most studies on silver dressings for nonhealing wounds did not show a significant reduction of infection when silver sulfadiazine cream or silver dressings were used. Wound healing was found to vary among the different studies reviewed, depending on the type of wounds included in the study and the exact dressing used.…”
Section: Wound Dressings Impregnated With Silver Nanoparticlesmentioning
confidence: 84%
See 1 more Smart Citation
“…The silver dressing did not increase the overall healing rate, but it was associated with quicker healing in larger and older ulcers. An extensive metastudy by Storm-Versloot et al 79 confirmed these findings in that most studies on silver dressings for nonhealing wounds did not show a significant reduction of infection when silver sulfadiazine cream or silver dressings were used. Wound healing was found to vary among the different studies reviewed, depending on the type of wounds included in the study and the exact dressing used.…”
Section: Wound Dressings Impregnated With Silver Nanoparticlesmentioning
confidence: 84%
“…Wound healing was found to vary among the different studies reviewed, depending on the type of wounds included in the study and the exact dressing used. 79 A chitosan-nanocrystalline silver dressing showed superior healing rates (89%) compared with silver sulfadiazine dressings (68%) and chitosan film (74%). 80 In addition, the chitosan-nanocrystalline silver dressing deposited far less silver than did conventional silver sulfadiazine, 80 thus demonstrating that the use of silver nanoparticles may be safer in reducing the incidence of argyria and argyremia (elevated silver concentration in the blood).…”
Section: Wound Dressings Impregnated With Silver Nanoparticlesmentioning
confidence: 97%
“…For instance, ionic-silver-containing alginate dressings demonstrated broad-spectrum in vitro activity against Candida albicans, E. coli, P. aeruginosa, S. aureus, b-haemolytic Streptococcus and strictly anaerobic bacteria (Hooper et al, 2012), and good clinical outcomes were described for carboxymethyl cellulose dressings with ionic silver (Beele et al, 2010). In contrast, a systematic review of the Cochrane Collaboration comparing silver-containing dressings against non-medicated dressings concluded that 'there is insufficient evidence to establish whether silver-containing dressings or topical agents promote wound healing or prevent wound infection' (Storm-Versloot et al, 2010). Polyurethane foam or biocellulose wound dressings containing 0.5 % PHMB were even more effective in reducing pain and bacterial burden in infected acute and chronic wounds compared with silver dressings (Eberlein & Assadian, 2010;Eberlein et al, 2012).…”
Section: Potential Use Of Cpc and Mstmentioning
confidence: 99%
“…In 2010, a Cochrane Review did not identify an association between the use of topical silver dressings and either promotion of wound healing or wound infection prophylaxis. 27 Within a decade of the widespread use of topical silver wound treatments, leukopenia was observed in patients with burn wounds treated with silver agents. 28 In addition to medical exposure, there are several acute and chronic routes of exposure to silver, including ingestion, inhalation, and dermal absorption.…”
Section: Discussionmentioning
confidence: 99%